Total luminescence (Chemiluminescence & Fluorescence)- FIA Method For The Determination of DL-Histidine - Shakir, I . M.A.; Turkie, N. S.; Ulaiwi, W. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Histidine was determined via measurement of total luminescence (i:e creation of chemiluminescence and insitu irradiation of released light to an acceptor fluorophore molecule to initiate fluorescence from fluorescien molecule in flat – spiral micro cell designed for this measurement . A detailed description of robust linear equation for the range of 0.002 – 0.05 mol.L-1 for a sample size of 70 µL with a correlation coefficient of 0.9879 and a coefficient of determination of 97.59% while for a quadratic model of the same concentration range was 0.9881 correlation coefficient and 97.63% coefficient of determination. Analysis of variance was conducted for both kinds of models . It indicated that their was no significant difference and both equations can be used to represent the data obtained